Probiotics use is associated with improved clinical outcomes among hospitalized patients with COVID-19. (August 2021) - Zhang, Lina; Han, Huanqin; Li, Xuan; Chen, Caozhen; Xie, Xiaobing; Su, Guomei; Ye, Shicai; Wang, Cuili; He, Qing; Wang, Fang; Huang, Fang; Wang, Zhaoqin; et al.
Background and aims: Currently, there are no definitive therapies for coronavirus disease 2019 (COVID-19). Gut microbial dysbiosis has been proved to be associated with COVID-19 severity and probiotics is an adjunctive therapy for COIVD-19. However, the potential benefit of probiotics in COVID-19 has not been studied. We aimed to assess the relationship of probiotics use with clinical outcomes in patients with COVID-19. Methods: We conducted a propensity-score matched retrospective cohort study of adult patients with COVID-19. Eligible patients received either probiotics plus standard care (probiotics group) or standard care alone (non-probiotics group). The primary outcome was the clinical improvement rate, which was compared among propensity-score matched groups and in the unmatched cohort. Secondary outcomes included the duration of viral shedding, fever, and hospital stay. Results: Among the propensity-score matched groups, probiotics use was related to clinical improvement rates (log-rank p  = 0.028). This relationship was driven primarily by a shorter (days) time to clinical improvement [difference, −3 (−4 to −1), p  = 0.022], reduction in duration of fever [−1.0 (−2.0 to 0.0), p  = 0.025], viral shedding [−3 (−6 to −1), p  < 0.001], and hospital stay [−3 (−5 to −1), p  = 0.009]. Using the Cox model with time-varying exposure, use of probiotics remained independently related to better clinical improvement rate in the unmatched cohort. Conclusion: Our study suggested that probiotics use was related to improved clinical outcomes in patients with COVID-19. Further studies are required to validate the effect of probiotics in combating the COVID-19 pandemic.